Factors affecting adoption of economic management practices in beef cattle production in Rio Grande do Sul state, Brazil. (December 2015) - Dill, Matheus Dhein; Emvalomatis, Grigorios; Saatkamp, Helmut; Rossi, João Augusto; Pereira, Gabriel Ribas; Barcellos, Júlio Otávio Jardim
Abstract: Beef cattle production in the Rio Grande do Sul State, Brazil, faces serious challenges due to low profitability and competition for alternative land uses. Despite this, many farmers have not yet adopted economic management practices as a support tool to enhance the competitiveness of their farms, due to differences related to lifestyle, values, customs, traditions and personal goals. We interviewed 73 farmers in order to understand the factors affecting the adoption of such practices. A probit model was estimated to identify farmers' characteristics, access to information, and production and economic characteristics that affect the adoption of economic management practices. Farmers with large landholdings and diversified production are less likely to adopt such practices. On the other hand, a number of factors, such as Internet access, participation in farmer associations, receiving technical assistance, number of cows bred annually, weaning rate greater than 70%, and utilization of the birth to slaughter system, positively affect the probability of adoption. Considering that few workshops and training programs on farm management are offered to farmers, the information presented in this study might be useful to motivate the development of extension programs, which take into account farmers' characteristics and, thus, achieve better results in terms of dissemination of economic management techniques. Highlights: Communication between farmers and technicians is key for diffusion of innovation. Farmers with a higher weaning rate are more likely to adopt farm economic management. The participation of farmers in producer associations positively affects technology adoption. Farmers that normally access the Internet are expected to adopt economic management.